Impact of Blighia sapida (k. Koenig) aril consumption on viscera and their functionalities - Howélé, Ouattara; Soualio, Kamagate; Baudoin, Kokore Angoua; Seraphin, Kati-Coulibaly (Open Science Journal, 2019)
The aim of this study was to understand the effects of Blighia sapida aril consumption on viscera and their functionalities. For this instance, quantities of arils were cooked (500 g/l) and lyophilize. Six homogeneous groups of young rats were fed ad libitum with six different diets which can be distinguished by the level of Blighia sapida aril powder put in the diet formulate. There were control diet (0% Blighia sapida arils powder), Bs1 (6.25% Blighia sapida arils powder), Bs2 (12.5% Blighia sapida arils powder), Bs3 (25% Blighia sapida arils powder), Bs4 (50% Blighia sapida arils powder) and Bs5 (75% Blighia sapida arils powder). At the end of the experimentation, blood samples were collected and were used for analyses of plasmatic bilirubin content. After sacrificed the experimental rats, stomach, liver, kidney, heart and lung were removed and weighted. These organs were processed for histopathological studies. There were no different variation (p>0.05) of bilirubin content between rats which received control diet and those which received the experimental diets. Organs weight of rats fed with diets Bs1, Bs2 and diet Bs3 were not globally different (p>0.05) compare to those of the control diet while organs weight of rats fed with diets Bs4 and Bs5 were globally reduced (p<0.05). No pathologies on viscera were observed when Blighia sapida aril powder is consumed with moderation (under a value of 50 % of nutrition value need). But, when consumed with exaggeration it provokes lipid nephrosis lesions on kidneys cells and necrosis on hepatic parenchyma. We can notice that Blighia sapida aril is rich nutritiously but it must be consumed with moderation in order to avoid pathologies on viscera.